2002
DOI: 10.1128/aem.68.11.5318-5325.2002
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Mycobacteria in Water Treatment Lines and in Water Distribution Systems

Abstract: The frequency of recovery of atypical mycobacteria was estimated in two treatment plants providing drinking water to Paris, France, at some intermediate stages of treatment. The two plants use two different filtration processes, rapid and slow sand filtration. Our results suggest that slow sand filtration is more efficient for removing mycobacteria than rapid sand filtration. In addition, our results show that mycobacteria can colonize and grow on granular activated carbon and are able to enter distribution sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
1
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 53 publications
(54 reference statements)
10
136
1
9
Order By: Relevance
“…The reasons for the enrichment of mycobacteria are not clear. Mycobacteria readily form biofilms and, because of their generally waxy quality, may be particularly resistant to shear forces generated in shower operation (28)(29)(30)(31)(32)(33)(34)(35)(36). Furthermore, many species of biofilm-forming mycobacteria are chlorineresistant, and thus potentially can be enriched by chlorine disinfection protocols used by many municipalities (28,29,34,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the enrichment of mycobacteria are not clear. Mycobacteria readily form biofilms and, because of their generally waxy quality, may be particularly resistant to shear forces generated in shower operation (28)(29)(30)(31)(32)(33)(34)(35)(36). Furthermore, many species of biofilm-forming mycobacteria are chlorineresistant, and thus potentially can be enriched by chlorine disinfection protocols used by many municipalities (28,29,34,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In a drinking-water treatment system, LE DANTEC et al 21 also reported the predominance of M. gordonae in post-filtration water. It should be noted that in our study the potentially pathogenic M. kansasii 3 was isolated three times; this species has been responsible for infections in immunodeficient patients 12 .…”
Section: Burkholderia Cepaciamentioning
confidence: 95%
“…Evidências de que na água as MA podem crescer e se manter nos sistemas de distribuição de ambientes hospitalares tem sido também descritas (Von Reyn et al, 1993;Von Reyn et al, 1994;Le Dantec et al, 2002 % t1 3 7 1 2 --------4 9 t2 10 24 4 10 1 2 4 10 2 5 1 2 22 54 t3 6 15 7 17 ------2 5 15 37 totais 19 46 12 29 1 2 4 10 2 5 3 7 41 100 Tabela 4 -Espécies de micobactérias isoladas de águas de torneiras do centro cirúrgico do Hospital Universitário getulio Vargas/AM. t1 = torneira 1; t2 = torneira 2; t3 = torneira 3; M = Mycobacterium.…”
Section: Resultsunclassified
“…Pesquisa de Micobactérias Ambientais em água de torneira, luvas e soluções utilizadas em procedimentos cirúrgicos no Hospital Universitário Getúlio vargas -Manaus/AM Alguns autores consideram que a existência de micobactérias nos sistemas de distribuição de água pode ser a forma de infectividade do ser humano (Von Reyn et al, 1993;Von Reyn et al, 1994;Le Dantec et al, 2002), fato esse amparado no reconhecimento das micobactérias como patógenos oportunistas (Vaerewijck et al, 2005). Assim, pacientes debilitados e/ou com soluções de continuidade na derme, estariam mais expostos a adquirir micobacterioses em ambientes hospitalares com sistema de distribuição de águas contaminados por micobactérias ambientais.…”
Section: Resultsunclassified